Ludwigia venugopalanii (Onagraceae), a striking apetalous species from Kerala, India - Arya, Sindhu; Suresh, Veerankutty; Biju, Punnakot; Vishnu, Walsan Kalarikkal; Anilkumar, Venugopalan Nair Saradhamma (Phytotaxa, 2020)
Ludwigia venugopalanii , a new species of Ludwigia from Western Ghats, Kerala (Southwestern India), is described and illustrated. The new species Ludwigia venugopalanii is morphologically similar to L. palustris from which it differs by alternate phyllotaxy, length and pubescence of calyx tube, absence of bracteoles, shape of ovule and capsule morphology.